Au–Cu2−xSe heterogeneous nanocrystals for efficient photothermal heating for cancer therapy. Issue 25 (2nd June 2017) - Zhu, Dewei; Liu, Maixian; Liu, Xin; Liu, Yang; Prasad, Paras N.; Swihart, Mark T.
Abstract : In this study, we show that Au–Cu2− x Se heterogeneous nanocrystals have great promise for use in photothermal therapy (PTT). Abstract : In this study, we show that Au–Cu2− x Se heterogeneous nanocrystals have great promise for use in photothermal therapy (PTT). Ligand-stabilized heterogeneous gold–copper selenide (Au–Cu2− x Se) hybrid nanocrystals were synthesized by a colloidal gold seed-mediated method. The nanocrystals exhibit broad localized surface plasmon resonance (LSPR) across visible and near-infrared (NIR) wavelengths, arising from interactions between the two nanocrystal domains. After a ligand-exchange process, the NCs readily disperse in water while retaining their LSPR absorbance. Upon illumination with a 980 nm laser, the Au–Cu2− x Se nanocrystals produced significant photothermal heating with a photothermal transduction efficiency comparable to that of larger gold nanostructures that have been widely studied for PTT. In vitro photothermal heating of Au–Cu2− x Se nanocrystals in the presence of human cervical cancer cells caused cell ablation after 10 min laser irradiation. Cell viability assays demonstrated that the hybrid nanocrystals are biocompatible at doses needed for photothermal therapy. Overall, these heterogeneous nanocrystals provide the NIR PTT efficacy of larger gold nanorods in a much smaller overall nanostructure that may have advantages with respect to biodistribution and clearance.